Perylene bisbenzimidazole nonlinear dielectric material for energy storage. Issue 1 (2nd January 2019) - Hein, Samuel J.; Edder, Carine; Kowalczyk, Marta; Borzenko, Andrey; Mourokh, Lev; Lazarev, Pavel
Abstract : We synthesized and characterized an organic molecule which can serve as a unit for high-density energy storage. Abstract : A novel perylene bisbenzimidazole comprising both donor and acceptor functional groups was designed, synthesized, and characterized. This structure exhibits potentially useful physical properties, including a nonlinear dielectric response to an increasing electric field. This material can be used in energy storage devices as the dielectric part of a capacitor. Energy storage devices based on film capacitors are targeting applications in a wide range of industrial, residential and transportation systems.